AN EASY AND SIMPLE METHOD OF ISOLATION AND PURIFICATION OF GENOMIC DNA FROM THE LEAVES OF GYMNEMA SYLVESTRE-AN ANTI-DIABETIC PLANT: Life Sciences-Molecular Biology - R, BALAMURALI KRISHNA; R, SUJITHA; JAVANGULA, HARIKA; D, SWAPNA; K, JAGADEESWARA REDDY (International Journal of Life Science and Pharma Research, 2012)
Gymnema sylvestre is a vine-like plant and is considered as herbal remedy for high blood sugar. The important active ingredient of Gymnema sylvestre is an organic acid called “Gymnemic acid”. Genomic DNA is the blue print of life, which is inherited and passed on from generation to generation directing the development of cells, organelles and organisms. Isolation of DNA, RNA and proteins is essential for all molecular biology investigations. The DNA isolation from plant tissues is very difficult due the presence of various secondary plant products. A protocol works with one plant group and may fail with the others. Hence a number of DNA isolation methods have been developed for different target plant groups. In the present study genomic DNA has been isolated and purified from young leaves of 17 ecotypes of Gymnema sylvestre with three different extraction methods i.e., modified CTAB method (method1), phenol-chloroform method (method 2), and Dellaporta method (method 3). Among the 3 methods tried, CTAB method was found to be suitable for PCR amplification with high purity and yield of genomic DNA.